Prominin‐like, a homolog of mammalian CD133, suppresses dilp6 and TOR signaling to maintain body size and weight in Drosophila. Issue 2 (11th October 2018) - Zheng, Huimei; Zhang, Yafei; Chen, Yuchen; Guo, Pengfei; Wang, Xuexiang; Yuan, Xin; Ge, Wanzhong; Yang, Ru; Yan, Qingfeng; Yang, Xiaohang; Xi, Yongmei
ABSTRACT: CD133 (AC133/prominin‐l) has been identified as a stem cell marker and a putative cancer stem cell marker in many solid tumors. Its biologic function and molecular mechanisms remain largely elusive. Here, we show that a fly mutant for prominin‐like, a homolog of mammalian CD133, shows a larger body size and excess weight accompanied with higher fat deposits as compared with the wild type. The expression levels of prominin‐like are mediated by ecdysone signaling where its protein levels increase dramatically in the fat body during metamorphosis. Prominin‐like mutants exhibit higher Drosophila insulin‐like peptide 6 (di lp6 ) levels during nonfeeding stages and increased Akt /Drosophila target of rapamycin (dTOR) signaling. On an amino acid‐restricted diet, prominin‐like mutants exhibit a significantly larger body size than the wild type does, similar to that which occurs upon the activation of the dTOR pathway in the fat body. Our data suggest that prominin‐like functions by suppressing TOR and dilp6 signaling to control body size and weight. The identification of the physiologic function of prominin‐like in Drosophila may provide valuable insight into the understanding of the metabolic function of CD133 in mammals.—Zheng, H., Zhang, Y., Chen, Y., Guo, P., Wang, X., Yuan, X., Ge, W., Yang, R., Yan, Q., Yang, X., Xi, Y. Prominin‐like, a homolog of mammalian CD133, suppresses di lp 6 and TOR signaling to maintain body size and weight in Drosophila . FASEB J. 33, 2646–2658 (2019). www.fasebj.org